Peran Dinas Kesehatan dalam Menurunkan Stunting di Kelurahan Singosari Kabupaten Gresik - Bagus Setyawan Nugraha; Lukman Arif (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Stunting is a persistent nutritional problem resulting from a long-term lack of nutritional intake, usually caused by unequal distribution of food and not meeting nutritional needs. Intrauterine growth restriction can manifest as stunting and become apparent when the child reaches two years of age. Stunting can affect individuals from early development to adulthood. Delays in the growth and development of toddlers due to stunting can have far-reaching impacts, including impaired cognitive capacity, increased risk of non-communicable diseases, decreased productivity, poverty, and increased chances of giving birth to babies with low birth weight. The aim of this research is to determine the role of the Health Service in reducing stunting. The method used is descriptive qualitative. Data collection techniques in this research are interviews, observation and documentation. Based on the research results that: 1. The role of the government as a regulator, regarding the problem of handling stunting toddlers, the rules made by the decision maker, namely the Regent, regarding stunting issues are quite good with these regulations, as well as the efforts made in handling stunting toddlers have been well monitored. , by providing coaching for 3 months and also providing additional food. 2. The government's role as a dynamist, treating stunted toddlers by conducting outreach and empowerment to handle and prevent the return of stunted toddlers. By conducting outreach either from social media or directly to the public, one of which is by posting on the media platform, namely Instagram. 3. The government's role as a facilitator, providing facilities and infrastructure as well as programs carried out in dealing with stunting toddlers, such as procuring body weighing equipment, height measuring instruments that are good and have accurate results.